2D Ultrashort Echo‐Time Functional Lung Imaging. Issue 6 (11th July 2020) - Balasch, Anke; Metze, Patrick; Stumpf, Kilian; Beer, Meinrad; Büttner, Susanne M.; Rottbauer, Wolfgang; Speidel, Tobias; Rasche, Volker
Abstract : Background: Imaging of the lung by MRI is challenging due to the intrinsic low proton density and rapid T2 * relaxation. MRI methods providing lung parenchyma and function are in demand. Purpose: To investigate the feasibility of two‐dimensional ultrashort echo‐time (2D UTE) imaging for lung function assessment. Study Type: Prospective. Population: Eleven healthy volunteers. Field Strength/Sequence: 3T, 2D tiny golden angle UTE (2D‐tyUTE). Assessment: The applicability of breath‐hold (BH) and self‐gated (SG) 2D‐tyUTE for quantification of the lung parenchyma signal‐to‐noise ratio (SNR), proton fraction ( f P ), fractional ventilation (FV), and perfusion ( f ) was investigated. Dependencies on repetition time (BHS/I1/I2 ) and respiratory phase (expiration [EX], inspiration [IN]) were investigated and compared between smokers and nonsmokers. Statistical Tests: Analysis of variance (ANOVA), Kendell's W. Results: Significant differences of SNR (EX: 10.98 ± 3.19(BHS ), 14.58 ± 3.89(BHI1 ), 17.59 ± 4.92(BHI2 ), 11.00 ± 5.42(SG); IN: 7.17 ± 2.07(BHS ), 9.51 ± 2.37(BHI1 ), 10.49 ± 2.33(BHI2 ), 10.00 ± 4.14(SG)) ( P  < 0.05 for all cases) were observed between the different approaches. Where f P in expiration (0.41 ± 0.13) was independent of the BH imaging technique, it was slightly higher in SG (0.44 ± 0.06). FV was reproducible among the BH techniques (0.41 ± 0.10), but significantly lower in SG (0.21 ± 0.06) ( P  < 0.05). A moderate correlation (R 2 = 0.47, P  < 0.01) was observed between the breathing amplitude and FV. No significant differences between BH and SG were observed for the perfusion analysis (EX: 3.50 ± 1.29 mL/min/mL [BHS ]; IN: 2.36 ± 1.05 mL/min/mL [BHS ]). Significant differences in f P were found between smokers (0.48 ± 0.11 BH) and nonsmokers (0.37 ± 0.12 BH) in expiration. Data Conclusion: This study demonstrates the feasibility of 2D‐tyUTE for successful quantification of relevant lung function parameters at 3T within clinically attractive acquisition times. The low spatial resolution into the slice selection direction may limit the final sensitivity and needs further clinical evaluation. Level of Evidence: 2 Technical Efficacy Stage: 1 J. MAGN. RESON. IMAGING 2020;52:1637–1644.